2013
DOI: 10.5539/jfr.v2n1p118
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Screw Extrusion Processing of Rainbow trout (Oncorhynchus mykiss) Feeds Using Graded Levels of High Protein Corn-Based Distillers Dried Grains (HP-DDG) and Conventional Distillers Dried Grains with Solubles (DDGS)

Abstract: Twin-screw extrusion cooking trials were performed to investigate the differential effects of conventional DDGS (DDGS) and HP-DDG inclusion, as fishmeal replacers, on physical properties (moisture content, water activity, thermal properties, expansion ratio, unit density, bulk density, water absorption, solubility and pellet durability indices, and color) of Rainbow trout (Oncorhynchus mykiss) feed. Four ingredient blends were formulated with 20 and 40% C-DDGS, and 20 and 40% HP-DDG, along with other required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Moreover, HP-DDG provides higher available phosphorous content thus reducing the need for phosphorous supplementation and its nutritional values are much more consistent than those of DDGS . Fallahi et al (2013) reported that inclusion of HP-DDG up to 40% led to the production of more expanded and floatable extrudates compared to those extrudates containing DDGS for rainbow trout. Soy is one of the most important protein-rich plants and a source of protein for aquafeeds (Morris et al, 2005;Francesco et al, 2007;Karalazos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HP-DDG provides higher available phosphorous content thus reducing the need for phosphorous supplementation and its nutritional values are much more consistent than those of DDGS . Fallahi et al (2013) reported that inclusion of HP-DDG up to 40% led to the production of more expanded and floatable extrudates compared to those extrudates containing DDGS for rainbow trout. Soy is one of the most important protein-rich plants and a source of protein for aquafeeds (Morris et al, 2005;Francesco et al, 2007;Karalazos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Assumptions made for fish feed productionThe system boundary for LCA does not include the transportation or emissions from freightTable 3.2. List of ingredients for fish feed production -Rainbow trout(Suleiman et al, 2015;Fallahi et al, 2012) Table 3.3. Variable costs input as determined by TEA for fish feed production There has been an increase in the population of people opting for gluten-free diets.…”
mentioning
confidence: 99%